Entangled empires the Anglo-Iberian Atlantic, 1500-1830 - Cañizares-Esguerra, Jorge,eeditor (University of Pennsylvania Press, 2018)
Entangled Empires emphasizes the connections between the English and Iberian imperial projects. The colonial history of the United States ought to be considered part of the history of colonial Latino-America just as Latin American history should be understood as fundamental to the constitution of the United States